2016
DOI: 10.1371/journal.pone.0147538
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Induces Altered Neuronal Differentiation by mGluR1 through PI3K-STAT3 Signaling in C17.2 Mouse Neural Stem-Like Cells

Abstract: Most studies of IR effects on neural cells and tissues in the brain are still focused on loss of neural stem cells. On the other hand, the effects of IR on neuronal differentiation and its implication in IR-induced brain damage are not well defined. To investigate the effects of IR on C17.2 mouse neural stem-like cells and mouse primary neural stem cells, neurite outgrowth and expression of neuronal markers and neuronal function-related genes were examined. To understand this process, the signaling pathways in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…A potential role of p53 in radiation-induced neuronal differentiation had previously also been suggested based on in vitro experiments 37,38 . We confirmed these results, and showed that irradiation of primary mouse NPCs (with 1 Gy of X-rays) diminished proliferation and induced differentiation from bipolar cells into multipolar neurons (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A potential role of p53 in radiation-induced neuronal differentiation had previously also been suggested based on in vitro experiments 37,38 . We confirmed these results, and showed that irradiation of primary mouse NPCs (with 1 Gy of X-rays) diminished proliferation and induced differentiation from bipolar cells into multipolar neurons (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Radiation-induced neuronal differentiation has been demonstrated in vitro 37,38,57,58 although the underlying mechanisms remained largely unclear. To our knowledge, this is the first study demonstrating the activation of a p53-dependent transcriptional program as a mechanism to induce neuronal differentiation in vivo , although a role for p53 in cellular differentiation in vivo has been previously proposed in mammary stem cells, the airway epithelium and cancer stem cells 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that a transient irradiation with X-rays (dose rate: 0.1 Gy/min, total dose: 500 mGy) promoted NGF-induced neurite extension in PC12 cells [ 3 ]. Similarly, low-dose-rate (0.95 Gy/min, total dose: 6 Gy) 137 Cs-γ radiation facilitated neurite extension in neural stem–like cells [ 4 ]. The cause of the difference between the results of promoting neuronal differentiation in the above-mentioned reports and the results of suppression of neuronal differentiation obtained in reports included in this study is not quite clear.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the difference between the results of promoting neuronal differentiation in the above-mentioned reports and the results of suppression of neuronal differentiation obtained in reports included in this study is not quite clear. The total irradiation doses used in studies on irradiation-induced inhibition of neurite extension, including the present study, range from 0.01 to 2.1 Gy [ 1 , 2 ], overlapping with those used in studies on the promotion of neurite extension, which range from 0.1 to 6 Gy [ 3 , 4 ]. In contrast, irradiation dose rates used in reports on the irradiation-induced inhibition of neurite extension range from 0.4 to 15 mGy/h [ 1 , 2 ], whereas those used in reports on the promotion of neurite extension range from 5 to 57 Gy/h [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation